BREZMEJNO MADŽARSKO JEZIKOSLOVJE. Éva Fancsaly – Erika Gúti – Miklós Kontra – Mónika Molnár Ljubić – Beatrix Oszkó – Beáta Siklósi – Orsolya Žagar Szentesi: A magyar nyelv Horvátországban / Madžarski jezik na Hrvaškem: Urednik: Miklós Kontra. Budapest–Eszék/Osijek: Gondolat Kiadó/Založba Gondolat– Media Hungarica Művelődési és Tájékoztatási Intézet/Kulturni in Informacijski Inštitut Media Hungarica 2016, 309 str. - Kolláth, Anna (Slavia Centralis, 2020)
The paper presents the fifth part of a series in which corpora relating to the Hungarian language of the outer regions were created, entitled A magyar nyelv a Kárpát-medencében a XX. század végén / Hungarian language in the Carpathian Basin at the end of the 20th century.